Smart Energy Management in Homes Using Fuzzy Logic - Moradi, Amir Mohammad; Osanloo, Roham; Tajari, Arad; Mansour Kiaee, Amir Hossein; Nozari, Shahan (Soft Computing Fusion with Applications, 2025)
With the rapid growth of energy consumption in residential buildings and the increasing associated costs, optimal energy management has become one of the primary necessities in today’s world. Traditional energy control methods fail to respond to dynamic changes and environmental uncertainties, while more complex methods like neural networks require extensive training data and heavy processing. Fuzzy logic, as an efficient tool, allows for smart decision-making in uncertain conditions by defining simple linguistic rules and processing vague data. This paper explores the practical application of this method in energy management, designing and implementing a system based on Arduino, analyzing performance results, and reviewing the fundamentals of fuzzy logic and smart home systems, comparing it with other existing methods. Results show that fuzzy logic can effectively reduce energy consumption and increase user comfort. In conclusion, the benefits, challenges, and future prospects of developing this approach are discussed.